PENGEMBANGAN METODE ANALISIS BENTUK DALAM PENGAJARAN SENI LUKIS DI JURUSAN PENDIDIKAN SENI RUPA FBS UNY - I Wayan Suardana (FBS UNY, 2009)
This study is aimed at identifying the effectiveness of form analysis method in the teaching of drawing art to the third semester students in Visual Art Education Study Program of FBS UNY. Form analysis uses a rational approach to visual art learning which is hoped to help the students in creating and thinking about drawing art. This research is queasy-experimental using nonequivalent control-group design. The population is the Visual Art Education students of 2007. The sample, which was 32 students, was intact: 18 are from class A as the experiment group and 14 from class B as the controlled group. The data analysis technique is covariant analysis to differentiate the mean of students' achievement in both groups, by considering their achievements in the previous semester. The result shows that significant difference exists in the mean of students' achievements of the experiment and controlled groups (F = 4,441, p = 0,043). In conclusion, the form analysis can improve the students' achievement in drawing art. Key words: form analysis method in the teaching of drawing art